The impacts of different habitats on the development of Telekia speiosa (Schreb.) Baumg. - Csabai, J.; Nagy, Z.; Tilly Mándy, A. (International Journal of Horticultural Science, 2010)
Telekia speiosa (Schreb.) Baumg. is a 100-150 cm high bushy perennial, which has yellow flowers and smells good. According to the descriptions (Farkas, 1999), it can be detected in two smaller areas within Hungary, namely in the Bükk hills and on the Szatmár-Bereg Plain. By the time of writing this paper, the population around Tiszabecs has already got extinct. Therefore, it is a protected relict species. It is named in honour of Sámuel Teleki, chancellor of Transylvania.Within the frame of the experiment, the Telekia speciosa (Schreb.) Baumg. was planted to places differently illuminated (sunny, semi shadow, shade), then the morphological changes brought about the various light conditions were investigated. The experiment was launched with a stock sown in October 2008. The seedlings were planted to three beds with diverse light conditions. The area of each bed was 1 m2, and ten seedlings were planted per m2. The parameters investigated are as follows: the length of leaf blade, the width of leaf blade, the length of petiole, the number of leaves per plant, and the alterations of leaves. As a result of our research, we can state that semi shadow is the optimal habitat for the plant. Under such ecological conditions the highest leaf production was observed, the leaves were species specific, healthy and big. The mean number of leaves per plant was 6.6, the mean length of blade was 16.6 cm, the mean width of blade was 13 cm, while the mean length of petiole was 14.2 cm. In the shade the plants grew poorly and the size of leaves were smaller. The mean number of leaves per plant was 4.1, the mean length of blade was 8.6 cm, the mean width of blade was 7.1 cm, and the mean length of petiole was 9.4 cm. In the sunny habitat a similarly high leaf production was observed as in the semi shadow; however, the leaves had brownish spots, they shriveled, feel rough, so they revealed a reduced aesthetical value. The mean number of leaves per plant was 6.6, the mean length of blade was 17.8 cm, the mean width of blade was 11.3 cm, and the mean length of petiole was 13.1 cm.